Exploratory propagatlon of Dendrocalamus hamiltonii Munro by One-Node Culm Cuttings - Sharma, O. P.; Kaushal, S. K. (Indian Forester, 1985)
Single node cuttings from node one to ten of 6-8-month-old culms planted horizontally in March, rooted at the nodes. The bud of a cutting produced a dominant routed shoot and/or a cluster of precocious branchlets. Later some of the buds on the precocious branchlets also produced rooted shoots. Cuttings from the basal node of two and one-year-old culms, planted in July-August gave similar but subdued results. Some of the cuttings from the remaining culm lengths produced erratically reeoted shoots (i) by rooting of mature primary beanches (ii) from primary-branch buds with or without air-layering and (iii) from buds of precocious-branchlet stumps. The rooted shoots produced from their basal buds juvenile culms, each with typical neck and rhizome.